Effect of Profitability and Solvency on Stock Prices With Dividend Policy as An Intervening Variable - august goenawan, yohanes; Subandriyo (Pandawan, 2023)
Research has the goal of being known and significantly analyzed whether stock prices gain influence from profitability and solvency through dividend policies by using several research variables to be analyzed, namely profitability and solvency ratios as free variables, stock prices as bound variables and the varied role of mediation using dividend policies. In this study the stick price used is the annual stock closing price, profitability is represented by ROA, solvency is represented by DER, and dividend policy is represented by DPR. The sample used as many as sixteen companies that always follow the LQ45 election. Analyze the data obtained using Structural Equation Modelling Partial Least Square with the help of Smart PLS 3.2.9 analysis tool. The study found that stock prices did not have a significant influence on profitability, DER and dividend policies. While on the dividend policy is considered unsuccessful to mediate the relationship of ROA and DER to the stock price.